(untitled) (Revista Venezolana de Salud Pública, 2021)
Abstract Emotional Intelligence (EI), as a set of individual skills to act and decide on the manifestation and regulation of emotions, based on one’s own well-being, has been considered as a factor for health prevention only for a few years. Using the literature review methodology, a sample of 20 publications was obtained in PubMed to discover research trends around the EI factor for disease prevention chronic diseases. The results of the review allow us to observe that, in reality, there are no studies specifically focused on EI for disease prevention; also, that the few studies located are generally dispersed in a series of diseases, physical and mental, that make classification difficult. The situation allows us to observe that the subject requires systematic research, which is in the process of strengthening.